Protective effects of Momordica grosvenori extract against lipid and protein oxidation-induced damage in dried minced pork slices. (November 2017) - Cheng, Jing-Rong; Liu, Xue-Ming; Zhang, You-Sheng; Zhang, Ye-Hui; Chen, Zhi-Yi; Tang, Dao-Bang; Wang, Jing-Yu
Abstract: The experiment was conducted to assess the protective effects of Momordica grosvenori extract (MGE) against lipid and protein oxidation-induced damage in vacuum-packed dried minced pork slices stored at room temperature for 21 days. Antioxidant activity of MGE was evaluated by measuring its radical scavenging activities and reducing power with progressive concentrations from 40 to 200 g/L. MGE was added to the dried minced pork slices at 7, 10 or 15 g/100 g. Results showed that inclusion of MGE in dried minced pork slice significantly delayed the formation of hexanal, thiobarbituric acid-reactive substances and carbonyls and reduced the sulfhydryl loss in a dose-dependent manner ( P < 0.05), indicating that MGE exerted a protective effect against lipids and protein oxidation. Concomitantly, an intense increase of redness and loss of lightness and yellowness was found to take place ( P < 0.05), though it exhibited little negative effects on the sensory properties of slices. Mogrosides, the main bioactive components in M. grosvenori, decreased primarily during processing while they were relatively stable during storage under vacuum condition, room temperature. All these results demonstrated MGE had great potential as a natural antioxidant used in meat products. Highlights: Protective effects of MGE against dried minced pork slices oxidation were studied. Antioxidant activity of MGE was evaluated. MGE could weaken lipid and protein oxidation of dried minced pork slice.